Perancangan Strategi Pengembangan Industri di Kabupaten Tangerang Berbasis Kompetensi INTI - Nurcahyo, Rahmat; Maemunsyah Z, Teuku Yuri; Muslim, Erlinda; Saparudin, . (SBM ITB, 2011)
The research purpose is to find core competence of Tangerang region for region development. Analythic Hierarchy Process (AHP) method is used to identify the core competence. Data collection is conducted through Focus Group Discussion (FGD) and quesioner by relevant experts. The result shows that Tangerang region core competence is textile and product textile industry.Interpretive Structural Modeling (ISM) then is used to develop the strategy for region development. While the strategy for development is 3 stages such as early stage through policy devepoment, main stage through machinery restructuring and human resource development, and final stage through productivity improvement and cluster strengthening.Keywords: core competence, Analythic Hierarchy Process (AHP), Interpretive Structural Modeling(ISM), textile and product textile industry, tangerang region